Analisis Pembiyaan Rahn Sebagai Produk Pembiyaan Yang Unggul Di Bank Mandiri Mitra Sukses Cabang Sidayu Gresik - Hanis Nofiyanti; Farhadi Arifiansyah (Program Studi Perbankan Syariah STAI Al-Fitrah Surabaya, 2023)
Rahn financing is a superior product at Bank Mitra Syariah Sidayu. So this study aims to see how Rahn's financing at Bank Mitra Syariah is more attractive to the people of Sidayu Gresik. In addition, why is Rahn's financing a superior product at Bank Mitra Syariah Sidayu Gresik? The research used is phenomenological qualitative research, namely research that explains or reveals the meaning of concepts or phenomena based on the awareness of experiences that occur in several individuals. The results of the study show that Rahn Financing is a superior product at Bank Mitra Syariah Sidayu because the service is very practical, fast, and easy and anti-complicated. High estimate, 4 months term (can be extended) and paid in installments. Cheap Ujroh fees start at 0.75% and are calculated daily, so it doesn't burden personal finances and safe pawn items.